Knowledge, perception and awareness of pineaplle growers in Muar, Johor towards pineapple mealybug wilt disease and management / Asma Khadijah Samsuri - Samsuri, Asma Khadijah (Faculty of Plantation and Agrotechnology, 2019)
Mealybug Wilt of Pineapple (MWP) disease caused by virus is one of the latest outbreaks of disease attacking pineapple crop (Ananas comosus). The fact of MWP disease among the pineapple growers is important to determine the effective management in controlling this disease. Unfortunately, the information of MWP disease is still limited especially in Muar, Johor. Therefore, the study was carry out to access farmer’s knowledge, perception and awareness on their management for controlling the disease. The structured questionnaires were distributed to 132 pineapple growers in Muar, Johor. Some analyses were used to analyze the data including descriptive, correlation and regression analysis. The results of survey revealed that most of farmers possess knowledge on MWP disease. Besides, farmer’s knowledge was the most factor that influenced their management practice compared to their perception toward this disease at beta rate 68.4%. Meanwhile, for disease management most of farmers showed that they were commonly use healthy plant materials, harvest pineapple fruits from healthy mother plants and destroy the infected plants with mealybug wilt disease. In addition, the farmers also indicated that higher disease incidence of MWP was in Josaphine pineapple variety than Moris Gajah and Moris. Furthermore, the disease severity was higher during vegetative stage of pineapple growth than other stages. Overall, the objectives of this study were achieved in determining farmer’s knowledge, perception and awareness on the incidence and severity of the disease with their management of MWP disease.